A case of SARS-CoV-2 reinfection in a patient with obstructive sleep apnea managed with telemedicine. Issue 2 (1st February 2021) - Sicsic Jr, Isabelo; Chacon, Andres R; Zaw, Moe; Ascher, Kori; Abreu, Alexandre; Chediak, Alejandro
Abstract : The novel coronavirus (SARS-CoV-2) has produced millions of infections and deaths worldwide. It is believed that adaptive immunity to the virus occurs although with variation in its pattern and duration. While uncommon, confirmed reinfection with the novel coronavirus has been reported. Telemedicine has emerged as a viable tool for the delivery of healthcare in lieu of in-person patient contact. The variable and occasionally rapid course of clinical disease raises safety concerns of using telemedicine in the clinical management of acute infection with the novel coronavirus. We present a case of novel coronavirus infection in an immunocompetent individual with obstructive sleep apnea (OSA) who failed to manifest an adaptive immune response to acute infection and was subsequently reinfected. The case highlights the use of telemedicine in managing novel coronavirus respiratory disease and the potential role of OSA as a disease facilitator.